Optimization of Charging Strategy by Prevention of Lithium Deposition on Anodes in high-energy Lithium-ion Batteries – Electrochemical Experiments. (1st October 2015) - Waldmann, Thomas; Kasper, Michael; Wohlfahrt-Mehrens, Margret
Abstract: The study evaluates the capacity fade of commercial 3.25 Ah 18650-type cells with NCA cathodes and graphite anodes quantitatively for different temperatures and charging strategies. For standard constant current / constant voltage (CC-CV) charging, the aging rate for cells cycled at 0.5C is increased with decreasing temperature in the range of 25 °C to 0 °C. Interestingly, no accelerated aging is observed for CC-CV charging in the temperature range of 25 °C to 60 °C at 0.5C. The observed behavior indicates lithium deposition on anodes for temperatures up to ∼25 °C and is further investigated by reconstruction of anode and cathode from the commercial 18650-type cells into full cells with an additional lithium metal reference electrode. The reconstruction method is scrutinized regarding its validity. Measurements with the reconstructed cells at 25 °C reveal the quantitative dependency of the anode potential vs. Li/Li + from the charge C-rate and cell voltage. This allows deriving charging strategies involving strictly positive anode potentials to avoid lithium deposition and preventing the corresponding capacity fade.